Evaluating the suitability of ELT textbooks for seventh graders in Kurikulum Merdeka: A study using Mukundan and Nimehchisalem's checklist - Rahman, Nadya Septiani; Robiasih, RR. Hasti; Sukur, Silvester Goridus (Universitas Sarjanawiyata Tamansiswa, 2024)
This study is an evaluation research and aimed to accomplish two objectives: (1) to assess the extent to which the English textbooks utilized by seventh-grade teachers meet the criteria of a good textbook based on Mukundan and Nimehchisalem's standards, and (2) to identify the strengths and weaknesses of the two English textbooks used by seventh-grade teachers. The data were gathered through document analysis, questionnaires, and interviews. Subsequently, the data were analyzed and presented in a descriptive qualitative by utilizing Miles, Huberman, and Saldana's data analysis model (2014). The study focused on two textbooks, namely English for Nusantara and Bright: An English, which were evaluated using Mukundan and Nimehchisalem's checklist (2015). To ensure the validity of the evaluation results, two respondents served as inter-raters, they are an English teacher and a textbook reviewer. The findings of the study revealed various strengths and weaknesses in the two textbooks. English for Nusantara should take into consideration its layout, completeness of media, and clarity of instructions. Nonetheless, this textbook excels in terms of catering to students' backgrounds, providing a variety of activities, and offering guidance for both teachers and students. On the other hand, Bright: An English is commendable for its critical thinking tasks, inclusion of mini projects, and high-quality printing. Areas that require attention are the number and variety of activities included in the textbook, as well as the absence of a teacher's book. The evaluation results concluded that Bright: An English achieved a higher fulfillment score compared to English for Nusantara, with average scores of 3.18 and 2.92, respectively. In general, both textbooks are considered highly valuable and suitable for use as Kurikulum Merdeka's instructional materials.